Manajemen Risiko Keamanan Aset Teknologi Informasi dengan Metode COBIT 2019 (Studi Kasus: Diskominfo Kabupaten Tangerang) - Nida Fadhilah; Yulhendri Yulhendri (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Information Technology (IT) asset security is a fundamental aspect in sustaining the operational continuity of an organization, particularly within the government sector. The Tangerang Regency Communication and Information Agency (Diskominfo), as the entity responsible for managing regional information systems, is required to apply sound risk management practices to protect IT assets from various threats. This study aims to identify, assess, and manage IT asset security risks by applying the COBIT 2019 framework, which provides a structured approach to IT governance and management. The research methods employed include literature review, interviews, and analysis of IT security policies and procedures in place at Diskominfo Tangerang Regency. IT asset security was examined based on relevant domains within COBIT 2019, with emphasis on risk management processes and information security controls. The findings of this study are expected to yield strategic recommendations for Diskominfo Tangerang Regency in strengthening the effectiveness of IT asset security risk management and ensuring adherence to applicable IT governance standards